Characterization of a chondroitin 4-sulfate proteoglycan carrier for heparin neutralizing activity (platelet factor 4) released from human blood platelets - Barber, A.J.; Käser-Glanzmann, R.; Jakábová, M.; Lüscher, E.F. (Biochimica et biophysica acta, 1972)
Platelet heparin neutralizing activity (platelet factor 4) is released from human blood platelets by thrombin in the form of a high molecular weight proteoglycan-platelet factor 4 complex. This complex was partially purified by isoelectric precipitation and gel filtration. At high ionic strength ( I = 0.75) the complex dissociates into the active component (mol. wt 29000) and the proteoglycan carrier. The components were separated by gel filtration and the proteoglycan further purified by Na 2SO 4 treatment. The molecular weight of the purified carrier was 59000. The carbohydrate moieties of the proteoglycan isolated after papain digestion and ion-echange chromatography were shown to consist of chondroitin 4-sulfate by chemical, physical and electrophoretic analysis. The multichain proteoglycan consists of four chondroitin 4-sulfate chains (mol. wt 12000) in covalent linkage to a single polypeptide. The molecular weight (350000) of the fully saturated proteoglycan carrier suggests that 4 moles of platelet factor 4 are bound per mole of proteoglycan and that the carrier occurs in the form of a dimer consisting of 8 moles of platelet factor 4 and 2 moles of proteoglycan. The isolated chondroitin 4-sulfate moieties combine with platelet factor 4 at a binding ratio of one mole of platelet factor 4 per carbohydrate chain. Heparin completely displaces platelet factor 4 from both the saturated proteoglycan and chondroitin 4-sulfate complexes. Heparitin sulfate, dermatan sulfate and chondroitin 6-sulfate also combine stoichiometrically with platelet factor 4 and are displaced by equimolar amounts of heparin. Hyaluronic acid did not combine with platelet factor 4. The relative binding capacities of glycosaminoglycans for platelet factor 4 were shown to be: heparin (100), heparitin sulfate (75), chondroitin 4-sulfate (50), dermatan sulfate (50), chondroitin 6-sulfate (50), and hyaluronic acid (o). Chondroitin 4-sulfate was identified as the major glycosaminoglycan in all platelet subcellular fractions; in addition, the soluble fraction contains a minor amount of hyaluronic acid. Subcellular distribution studies revealed that 55% of both the proteoglycan carrier and platelet factor 4 activity were localized in the “granule rich” fraction. This data together with the low recovery of both these components in the membrane fraction, suggest that they occur together as a complex within specific granules and are released in this form under physiologic conditions.